2017
DOI: 10.1186/s12877-017-0616-z
|View full text |Cite
|
Sign up to set email alerts
|

Informed decision-making with and for people with dementia – efficacy of the PRODECIDE education program for legal representatives: protocol of a randomized controlled trial (PRODECIDE-RCT)

Abstract: BackgroundIn Germany, the guardianship system provides adults who are no longer able to handle their own affairs a court-appointed legal representative, for support without restriction of legal capacity. Although these representatives only rarely are qualified in healthcare, they nevertheless play decisive roles in the decision-making processes for people with dementia. Previously, we developed an education program (PRODECIDE) to address this shortcoming and tested it for feasibility. Typical, autonomy-restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The ethics committee of the German Society of Nursing Science approved the study. Details of the trial design and rationale have been reported previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethics committee of the German Society of Nursing Science approved the study. Details of the trial design and rationale have been reported previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…At T1 (at the end of/up to 2 weeks after the intervention), the primary outcome knowledge was assessed. The questionnaire was developed and pretested with a before-after design [ 20 , 22 ]. It comprises thirteen multiple choice items (four choices, with only one correct answer each) on the understanding of decision-making processes (two items), on quality and validity of study results (two items) and on realistic expectations regarding probabilities of benefits and harms of a PEG, PRs and APs to people with dementia (three items per intervention).…”
Section: Methodsmentioning
confidence: 99%
“…Considering there is an inconsistent variety of wording for these concepts such as proxy, surrogate, or representative (Fetherstonhaugh et al, 2017;Kwak et al, 2016;Lühnen et al, 2017), we propose the term representatives' shared decision-making (RSDM) for our paper, as the word Representative best fits in the legal sense addressed in this study. We define RSDM as follows:…”
Section: Shared Decision-making -Role Of Representativesmentioning
confidence: 99%